Accessibility to Tertiary Education Trust Fund (TETfund) and Effect on Academic Staff Job Performance in Southwest Universities, Nigeria - Olufunmilola , Olorunsola E.; Christianah, Aina A. (Journal of Education and Practice, 2023)
Purpose: The study examined the accessibility to Tertiary Education Trust Fund (TETfund) interventions and its effect on academic staff job performance in universities in Southwest, Nigeria. Methodology: Descriptive survey research design was adopted for the study. The population consisted of 11864 Nigeria public universities academic staff. Nine hundred and twenty-seven (927) universities' academic staff constituted the sample for the study. TETfund Interventions Questionnaire (TIQ) was administered on other academic staff while Academic Staff Job Performance Questionnaire (ASJPQ) was used by Heads of Departments (HODs) to assess the performance of academic staff. The face and content validity of instruments were ensured by experts in test and measurements. The consistency of the instruments was carried out using test-retest method. Coefficients of 0.86 and 0.87 were obtained for TIQ and ASJPQ respectively. Research question was answered using frequency counts and mean. Hypotheses were tested using Pearson Product Moment Correlation coefficient (PPMC). All hypotheses were tested at 0.05 level of significance. Results: The results revealed that there was a positive relationship between research, conference, further study grants and academic staff job performance. It also revealed that the universities and the academic staff cannot easily access research grant, conference attendance grant and further study grant that are provided through TETFund. Unique Contribution to Theory, Policy and Practice: The study has been able to make case for the review of policy frameworks of TETFund in order to make more impact in the area of knowledge creation and sharing. Furthermore, the interventions that are needed to guarantee optimal outputs from university academic staff were identified.